Discovery of nanomolar dengue and West Nile virus protease inhibitors containing a 4-benzyloxyphenylglycine residue - Behnam, Mira A. M.; Graf, Dominik Korbinian; Bartenschlager, Ralf; Zlotos, Darius P.; Klein, Christian D. (Journal of medicinal chemistry, 2015)
The dengue virus (DENV) and West Nile Virus (WNV) NS2B-NS3 proteases are attractive targets for the development of dual-acting therapeutics against these arboviral pathogens. We present the synthesis and extensive biological evaluation of inhibitors that contain benzyl ethers of 4-hydroxyphenylglycine as non-natural peptidic building blocks synthesized via a copper-complex intermediate. A three-step optimization strategy, beginning with fragment growth of the C-terminal 4-hydroxyphenylglycine to the benzyloxy ether, followed by C- and N-terminal optimization, and finally fragment merging generated compounds with in vitro affinities in the low nanomolar range. The most promising derivative reached Ki values of 12 nM at the DENV-2 and 39 nM at the WNV proteases. Several of the newly discovered protease inhibitors yielded a significant reduction of dengue and West Nile virus titers in cell-based assays of virus replication, with an EC50 value of 3.4 μM at DENV-2 and 15.5 μM at WNV for the most active analogue.